Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages 2 7. That the District Committees be entitled to investigate other points besides those mentioned in the Almoner's note, if they find it necessary for purposes of verification or on account of special circumstances arising out of the particular case. 8. That the District Committees send their reports to the Almoners as soon as the necessary information can be obtained, not waiting until their next meeting. 1. That for six months,* as an experiment, cases of outpatients or casualty patients be referred to District Committees by the Almoners of the Royal Free Hospital, the St. George's Hospital, and the Westminster Hospital for friendly visiting, with a view to carrying out any scheme of help apart from material relief which the member of the medical staff who is treating the case may think desirable for the ultimate cure of the patient. 2. That in each case in which a friendly visit is desired the Almoner forward to the proper District Committee the hospital case-papers, and state the object which she has in view in asking that the patient should be visited. 3. That the Visitors make it clear to the patient that they come on behalf of the Almoner of the hospital, and, if necessary, explain the arrangement made between the hospital and the Charity Organisation Society. 4. That the case be indexed at the office of the Committee, and placed in the hands of a Visitor by the Hon. Secretary or Secretary of the Committee, and that the result of the visits be recorded and filed in the office. 5. That Visitors undertaking this work be not necessarily members of Committee. 6. That the case be not dealt with except by friendly visiting unless, after communication with the Almoner, the Visitor considers that application should be made to the Committee for material assistance, and the patient makes such application. 7. That the report of the Visitor be forwarded by the Secretary with the hospital case-papers to the Almoner, a copy of the report being filed in the office in the ordinary way. 8. That any Visitor who intends to visit a patient on behalf of an Almoner at a hospital independently of the District Committee should, before visiting, inquire if the case is known to the Committee. * It is suggested that the six months should commence on April 1 next. 378/IMSW/A/1/1/9